2020
DOI: 10.1101/2020.04.17.046011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of TRPV1 in colonic mucin production and gut microbiota profile

Abstract: 1 8 PURPOSE: This study focuses on exploring the role of sensory cation channel Transient 1 9Receptor Potential channel subfamily Vanilloid 1 (TRPV1) in gut health, specifically mucus 2 0 3 1 address mucin production and gut microbiota related adverse effects during the development 3 2 of TRPV1 antagonism/ablation-based therapeutic and preventive strategies. 3 3

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…A reduced α-diversity was reported in KO mice, when compared to wild-type (WT) counterparts, as well as a β-diversity change by clustering several gut microbiota populations. At the phylum level, the Firmicutes/Bacteroidetes ratio diminished in KO mice, by reducing Firmicutes and enhancing Bacteroidetes abundance [100,101]. Moreover, ablation of TRPV1 neurons by the potent agonist resiniferatoxin induced a severe mucus level reduction, caused by the downregulation of multiple associated genes, and a reduction in the abundance of lactic acid-producing bacteria [101].…”
Section: Modulation Of the Gut Microbiota By Capsaicinmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced α-diversity was reported in KO mice, when compared to wild-type (WT) counterparts, as well as a β-diversity change by clustering several gut microbiota populations. At the phylum level, the Firmicutes/Bacteroidetes ratio diminished in KO mice, by reducing Firmicutes and enhancing Bacteroidetes abundance [100,101]. Moreover, ablation of TRPV1 neurons by the potent agonist resiniferatoxin induced a severe mucus level reduction, caused by the downregulation of multiple associated genes, and a reduction in the abundance of lactic acid-producing bacteria [101].…”
Section: Modulation Of the Gut Microbiota By Capsaicinmentioning
confidence: 99%
“…At the phylum level, the Firmicutes/Bacteroidetes ratio diminished in KO mice, by reducing Firmicutes and enhancing Bacteroidetes abundance [100,101]. Moreover, ablation of TRPV1 neurons by the potent agonist resiniferatoxin induced a severe mucus level reduction, caused by the downregulation of multiple associated genes, and a reduction in the abundance of lactic acid-producing bacteria [101]. Thus, TRPV1 may be essential for proper mucin production and for the preservation of a healthy gut bacterial population.…”
Section: Modulation Of the Gut Microbiota By Capsaicinmentioning
confidence: 99%
“…In one case, these beneficial and gut-microbiota-mediated effects of capsaicin were shown to be due to counteracting the CB1 overactivation by endocannabinoids in obesity [ 39 ]. However, in only a few of these experimental studies, the role of TRPV1, which is the major target for capsaicin, was investigated and demonstrated [ 41 ], despite the fact that also this ligand-activated channel is known to be strongly implicated in several aspects of energy metabolism control, ranging from food intake and satiety mechanisms to adipogenesis, white adipocyte browning and brown adipocyte activation [ 25 , 61 , 62 , 63 , 64 ]. In the present study, we assessed the effects of a 12 weeks dietary supplementation of CAE (equivalent to 4 mg capsaicinoids/day, of which 2.4 mg were capsaicin, 1.4 mg were dihydrocapsaicin and 0.2 mg were nordihydrocapsaicin) in reproductive-aged women with overweight and obesity undergoing a calorie-reduced diet (−500 kcal/day) on the gut microbiota and the expanded endocannabinoid system known as the eCBome.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, capsaicin modulates the gut microbiota population, which represents a critical factor for the anti-obesity effects that are exerted by this natural compound, contributing to improving glucose homeostasis through increasing short-chain fatty acids, regulating gastrointestinal hormones and inhibiting pro-inflammatory cytokines [ 39 , 40 ]. A very recent study suggested that such effects might be at least in part mediated by the activation of TRPV1 since the ablation of this ligand-activated channel from the rat intestine was found to cause gut dysbiosis, as evidenced by the decreased abundance of beneficial taxa and production of short-chain fatty acids, and by the impairment of colonic mucus secretion [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that TRPA1 agonist cinnamaldehyde induced HCO 3-secretion in colon, which is essential for mucus release 11 . Recently published work from our laboratory demonstrated that systemic TRPV1 ablation leads to impaired mucus secretion and causes dysbiosis in the gut 12 . Given the importance of TRPA1 and TRPV1 in gut mucin-immune axis, we hypothesize that the strategies of blocking (with antagonists) or desensitizing sensory nociceptive neuronal TRPV1 and TRPA1 for the treatment of IBD might impair colonic mucin homeostasis, leading to increased gut permeability and dysbiosis.…”
Section: Introductionmentioning
confidence: 99%